Country train - Beim, Jerrold 1910-1957.; Shortall, Leonard W. (New York Morrow, 1950)
A boy enjoys his ride on the Old Putt, the country train, and prefers it to the fancy new doubledecker streamliner.
Keywords: Railroads -- Trains -- Fiction